Disruption of G3BP1 granules promotes mammalian CNS and PNS axon regeneration - Pabitra K. Sahoo; Manasi Agrawal; Nicholas Hanovice; Patricia J. Ward; Meghal Desai; Terika P. Smith; HaoMin SiMa; Jennifer N. Dulin; Lauren S. Vaughn; Mark H. Tuszynski; Kristy Welshhans; Larry I. Benowitz; et al. (Proceedings of the National Academy of Sciences, 2025)
Depletion or inhibition of core stress granule proteins, G3BP1 in mammals and TIAR-2 in Caenorhabditis elegans , increases the growth of spontaneously regenerating axons. Inhibition of G3BP1 by expression of its acidic or “B-domain” accelerates axon regeneration after nerve injury, bringing a potential therapeutic strategy for peripheral nerve repair. Here, we asked whether G3BP1 inhibition is a viable strategy to promote regeneration in injured mammalian central nervous system (CNS) where axons do not regenerate spontaneously. G3BP1 B-domain expression was found to promote axon regeneration in the transected spinal cord provided with a permissive peripheral nerve graft (PNG) as well as in crushed optic nerve. Moreover, a cell-permeable peptide (CPP) to a subregion of B-domain (rodent G3BP1 amino acids 190 to 208) accelerated axon regeneration after peripheral nerve injury and promoted regrowth of reticulospinal axons into the distal transected spinal cord through a bridging PNG. G3BP1 CPP promoted axon growth from rodent and human neurons cultured on permissive substrates, and this function required alternating Glu/Asp-Pro repeats that impart a unique predicted tertiary structure. The G3BP1 CPP disassembles axonal G3BP1, G3BP2, and FMRP, but not FXR1, granules and selectively increases axonal protein synthesis in cortical neurons. These studies identify G3BP1 granules as a key regulator of axon growth in CNS neurons and demonstrate that disassembly of these granules promotes retinal axon regeneration in injured optic nerve and reticulospinal axon elongation into permissive environments after CNS injury. This work highlights G3BP1 granule disassembly as a potential therapeutic strategy for enhancing axon growth and neural repair.